1994
DOI: 10.1037/0022-006x.62.6.1204
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral self-regulation in adolescents with Type I diabetes: Negative affectivity and blood glucose symptom perception.

Abstract: The hypothesis that negative affectivity (NA) is associated with accuracy of blood glucose (BG) symptom perceptions and diabetes control was assessed. After completing measures of BG symptom beliefs and NA-related constructs (i.e., attentional focus and trait anxiety), 35 adolescents with insulin-dependent diabetes monitored their physical symptoms and their actual BG levels 3 times daily for 2 weeks. Each subject's actual BG symptoms were determined by correlating symptom ratings with BG levels and were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 45 publications
(56 reference statements)
1
34
0
Order By: Relevance
“…Wiebe et al (9) reported that "negative affectivity," which was also described as a tendency to experience negative emotions, was related to worse glycemic control in a sample of adolescents with type 1 diabetes. The evidence was an observed interaction between measures of trait anxiety and "internal focus" based on a brief self-report measure of how much attention was paid to internal versus external cues for information about blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Wiebe et al (9) reported that "negative affectivity," which was also described as a tendency to experience negative emotions, was related to worse glycemic control in a sample of adolescents with type 1 diabetes. The evidence was an observed interaction between measures of trait anxiety and "internal focus" based on a brief self-report measure of how much attention was paid to internal versus external cues for information about blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety may also have more subtle effects on specific aspects of diabetes management. Individuals with T1DM who are high in trait anxiety show a tendency to misattribute bodily symptoms to hypoglycemia, which can lead to unnecessary treatment and hyperglycemia (Wiebe et al, 1994). In addition, needle phobias and fear of self-injecting/testing, which have an obvious potential impact on diabetes management, persist undetected in some patients long after diagnosis (Snoek, Mollema, Heine, Bouter, & van der Ploeg, 1997).…”
Section: Individual Variablesmentioning
confidence: 99%
“…For example, Wiebe, Alderfer, Palmer, Lindsay, and Jarrett (1994) found that trait anxiety significantly influenced symptom perception and interpretation among adolescents with Type 1 diabetes. These findings suggest that further study of personality dimensions in the management and progression of chronic illness in adolescence is warranted.…”
Section: Developmental Perspective On Chronic Illness During Adolescencementioning
confidence: 99%